A BAC-Based Physical Map of the Major Autosomes of Drosophila melanogaster - Hoskins, Roger A.; Nelson, Catherine R.; Berman, Benjamin P.; Laverty, Todd R.; George, Reed A.; Ciesiolka, Lisa; Naeemuddin, Mohammed; Arenson, Andrew D.; Durbin, James; David, Robert G.; Tabor, Paul E.; Bailey, Michael R.; et al. (Science (American Association for the Advancement of Science), 2000)
We constructed a bacterial artificial chromosome (BAC)-based physical map of chromosomes 2 and 3 of Drosophila melanogaster, which constitute 81% of the genome. Sequence tagged site (STS) content, restriction fingerprinting, and polytene chromosome in situ hybridization approaches were integrated to produce a map spanning the euchromatin. Three of five remaining gaps are in repeat-rich regions near the centromeres. A tiling path of clones spanning this map and STS maps of chromosomes X and 4 was sequenced to low coverage; the maps and tiling path sequence were used to support and verify the whole-genome sequence assembly, and tiling path BACs were used as templates in sequence finishing.